Tawhidic paradigm and economic policies on halal tourism for sustainable wealth creation in Malaysia - Mhd. Sarif, Suhaimi; Ismail, Yusof (2015)
This study examines the perceived effects of Tawhidic paradigm on economic policies in relation to the promotion of the growth of halal tourism industry for sustainable wealth creation in Malaysia. Tawhidic paradigm offers economic policy thinking that is guided by the principles of Qur’an and Sunnah in formulating and implementing policy blueprints and instruments. In contrast, the current policy thoughts are guided by market forces and sentiments which contribute to speculative uncertainties. A proposed index of Tawhidic paradigm policy thinking and process is developed to ascertain the level of intensity of Tawhidic based policy thinking and practices at three levels - policy making, implementation and evaluation. This study uses personal interviews with economic policy makers, key representatives from halal industry trade associations, and selected halal tourism operators. Preliminary findings disclose that the economic policies on halal tourism reflect some levels of Tawhidic paradigm but nevertheless inadequate to sustain wealth creation.